The Ubiquitous Choline Transporter SLC44A1 - Michel, Vera; Bakovic, Marica (Central Nervous System Agents in Medicinal Chemistry, 2012)
Choline is a zwitter ion that is positively charged at certain pH, which necessitates transport systems to allow this amine to cross the phospholipid bilayer of cellular membranes. The solute carrier 44A1 (SLC44A1), also referred to as choline transporter-like protein 1 (CTL1), is a recently discovered choline transporter with an intermediate affinity for choline; this transport is Na+-independent and sensitive to inhibition by the drug hemicholinium-3. We highlight in this review the discovery and characterization of SLC44A1, describe its expression patterns and subcellular localization, and summarize evidence for the role of this choline transporter in the central nervous system.
Keywords: hemicholinium